2020
DOI: 10.1111/jfpp.14646
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation of roasted sweet potatoes influenced by different cultivars: A correlation study with respect to sugars, amino acids, volatile compounds, and colors

Abstract: In this study, color values, amino acid, and sugar composition (sucrose, fructose, glucose, and maltose) of fresh and roasted sweet potatoes from 11 cultivars were determined. Sensory evaluation (overall acceptability), GC‐MS, electronic nose, and electronic tongue were also used to analyze the flavor compounds and sensory index. The results of overall acceptability indicated that Yanshu No. 25 and Pushu No. 32 were preferred to the other ones. Besides, there was a certain correlation between colors, sugars, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…During roasting, peeled sweet potatoes' starch and polysaccharides will form a secondary crusty peel. The sweet potatoes undergoing the two treatments were dark brown due to the decrease in L* value and the increase in a* value, and the degree of browning rises rapidly [8]. After roasting for more than 2.5 h, the two sweet potatoes exhibited similar roasting effects, and both were brown with a hard-shell surface.…”
Section: Appearance and Color Analysismentioning
confidence: 93%
See 4 more Smart Citations
“…During roasting, peeled sweet potatoes' starch and polysaccharides will form a secondary crusty peel. The sweet potatoes undergoing the two treatments were dark brown due to the decrease in L* value and the increase in a* value, and the degree of browning rises rapidly [8]. After roasting for more than 2.5 h, the two sweet potatoes exhibited similar roasting effects, and both were brown with a hard-shell surface.…”
Section: Appearance and Color Analysismentioning
confidence: 93%
“…The volatile composition of roasted sweet potatoes was modified from Hou et al [8] and identified with an HP-6890 gas chromatograph combined with a 5973 Turbo Pump Mass Selective Detector (MSD), and a DB-wax capillary column (60 m × 0.25 mm × 0.25 µm), were purchased by Agilent Technologies Co. (Santa Clara, CA, USA). Each 1.5 g sample was heated to 60 • C in a vial and the headspace was sampled with a DVB/CAR/PDMS fiber (Supelco Inc., Bellefonte, PA, USA) for 60 min.…”
Section: Gc/ms Analysismentioning
confidence: 99%
See 3 more Smart Citations